Manajemen Risiko Kepatuhan Syariah Serta Implementasinya pada Bank Syariah Indonesia (BSI) - Faizatul, Zelyn; Faizal, Muhazzab Alief; Asiyah, Binti Nur; Subagyo, Rohmad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The background of this research is the potential of Islamic banking in Indonesia which is followed by very good developments. However, this research wants to look deeply into the implementation of sharia compliance by sharia banking, especially Indonesian Sharia Banks. Based on this, the research objectives include knowing the application of sharia, in this case, BSI compliance in making sharia principles a guideline for banking operations and management. As well as BSI's efforts to realize sharia compliance through sharia compliance management which is separate from other management. The research was carried out using a qualitative method with a literature study, where the literacy used was books, research journals that are appropriate to the topic of discussion, as well as the annual financial reports of Bank Syariah Indonesia. The results of the study found that the individual and integrated BSI risk profile until 2022 shows that BSI risk can be managed properly to support future business development. In other words, BSI has implemented risk management appropriately and adequately. Keywords: Sharia Banking; Sharia Compliance; Indonesian Sharia Bank